Role of synovial lymphatic function in osteoarthritis. Issue 9 (September 2022) - Cao, M.; Ong, M.T.Y.; Yung, P.S.H.; Tuan, R.S.; Jiang, Y.
Summary: Background: Osteoarthritis (OA) affects the entire joint, initially with a low degree of inflammation. Synovitis is correlated with the severity of OA clinical symptoms and cartilage degradation. The synovial lymphatic system (SLS) plays a prominent role in clearing macromolecules within the joint, including the pro-inflammatory cytokines in arthritic status. Scattered evidence shows that impaired SLS drainage function leads to the accumulation of inflammatory factors in the joint and aggravates the progression of OA, and the role of SLS function in OA is less studied. Design: This review summarizes the current understanding of synovial lymphatic function in OA progression and potential regulatory pathways and aims to provide a framework of knowledge for the development of OA treatments targeting lymphatic structure and functions. Results: SLS locates in the subintima layer of the synovium and consists of lymphatic capillaries and lymphatic collecting vessels. Vascular endothelial growth factor C (VEGF-C) is the most critical regulating factor of lymphatic endothelial cells (LECs) and SLS. Nitric oxide production-induced impairment of lymphatic muscle cells (LMCs) and contractile function may attribute to drainage dysfunction. Preclinical evidence suggests that promoting lymphatic drainage may help restore intra-articular homeostasis to attenuate the progression of OA. Conclusion: SLS is actively involved in the homeostatic maintenance of the joint. Understanding the drainage function of the SLS at different stages of OA development is essential for further design of therapies targeting the function of these vessels.